2019
DOI: 10.1021/acs.jctc.9b00476
|View full text |Cite
|
Sign up to set email alerts
|

Excited States with Selected Configuration Interaction-Quantum Monte Carlo: Chemically Accurate Excitation Energies and Geometries

Abstract: We employ quantum Monte Carlo to obtain chemically accurate vertical and adiabatic excitation energies, and equilibrium excited-state structures for the small, yet challenging, formaldehyde and thioformaldehyde molecules. A key ingredient is a robust protocol to obtain balanced ground- and excited-state Jastrow–Slater wave functions at a given geometry, and to maintain such a balanced description as we relax the structure in the excited state. We use determinantal components generated via a selected configurat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 74 publications
2
96
1
1
Order By: Relevance
“…Although among the employed trial wave functions, both of the SOCI‐J and SOCI‐J‐BF wave functions have computed the most accurate energies for the studied systems with similar accuracy. This characteristic feature is not seen in the other wave functions in the present or previous works. Despite very large computational cost, this method could provide efficient trial wave functions for different systems and states.…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…Although among the employed trial wave functions, both of the SOCI‐J and SOCI‐J‐BF wave functions have computed the most accurate energies for the studied systems with similar accuracy. This characteristic feature is not seen in the other wave functions in the present or previous works. Despite very large computational cost, this method could provide efficient trial wave functions for different systems and states.…”
Section: Resultscontrasting
confidence: 76%
“…The previous studies through using the single‐ and multideterminant trial wave functions show that the QMC methods could provide an accurate description for both the ground and excited state properties . However, these studies have revealed that there is a strong dependence between the accuracy of the obtained energies and the quality of the trial wave function in the ground and excited states.…”
Section: Introductionmentioning
confidence: 99%
“…Using expansions with matched PT2 corrections has recently been shown to lead to accurate QMC excitation energies also for a relatively small number of determinants. 9 (ii) We perform the expansion of the two states simultaneously, using a common set of orbitals [the excited-state CASSCF(6,10) orbitals] and obtain automatically matched PT2 energy corrections during the expansion. 9 For the retinal model where the ground and excited states have the same symmetry, we have only one set of orbitals for the CIPSI expansions.…”
Section: Computational Detailsmentioning
confidence: 99%
“… 10 12 Importantly, recent methodological advancements 13 16 have enabled the fast calculation of energy derivatives and the optimization of many thousands of parameters for the internally consistent computation of QMC wave functions and geometries in the ground and excited states. 9 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…Es gibt auch noch andere Ansätze,d ie füra ngeregte Zustände eine Annäherung an FCI-Genauigkeit bieten. [69,70] Beispielsweise kçnnen angeregte Zustände mit verschiedenen Va rianten des stochastischen Quanten-Monte-Carlo-Verfahrens (QMC) [71,72] oder dessen Kombinationen mit anderen Te chniken [73,74] berechnet werden. Beispiele fürA nwendungen sind Azobenzol, [75] Festkçrper [76] oder Modelle fürd en Chromophor von Retinal.…”
Section: Multi-konfigurations-und Multi-referenz-methodenunclassified